Board of Directors Characteristics and Firm Financial Performance in UAE - Al-Mashregy, Mohammed Hamood Hamood (2012)
The purpose of this study is to empirically examine the impact of corporate governance mechanisms (board characteristics) namely; board size, board of director's independence and CEO duality on the firm financial performance (ROA). For the purpose of this study, 60 non-financial listed companies have been chosen; 33 from Abu Dhabi Securities Exchange and 27 from Dubai Financial Market, all in UAE market context. The conduct of testing is controlled by firm size. Multiple regressions analysis is utilized in this study in order to achieve the research objectives. The findings show that factors of board characteristics namely; board size, board of director's independence and CEO duality, have different relations with firm financial performance.First,the finding showed that board size has positive significant impact on the firm financial performance (ROA). Secondly, it showed that the board of director's independence has no significant impact on the firm financial performance (ROA). Moreover,the finding showed that there is negative significant impact of CEO duality on the firm financial performance (ROA). Last but not least, the firm size as control variable has positive significant impact on the firm financial performance (ROA). Therefore, this study can clearly integrate the relationship between corporate governance mechanisms and firm financial performance, and it can help UAE authorities market to improve and enhance the firm financial performance.